The Oxford handbook of Berkeley - Rickless, Samuel Charles 1964- (Oxford handbooks online, 2022)
'The Oxford Handbook of Berkeley' is a compendious examination of a large number of topics in the philosophy of George Berkeley (1685-1753), Anglican Bishop of Cloyne, the famous idealist and most illustrious Irish philosopher. It includes contributions from thirty-four expert commentators on Berkeley's philosophy, some of whom provide a state-of-the-art account of his philosophical achievements, and some of whom place his philosophy in historical context by comparing it with the views of other philosophers (including predecessors, contemporaries, and successors)